Tea-polyphenols coatings on AZ31 and AZ91 magnesium alloys for degradation control and improvement of the biological response - Ferraris, S.; Spriano, S.; Gamna, F.; Saqib, M.; Beshchasna, N.; Opitz, J.; Boccaccini, Aldo R.; Ünalan, Irem; Naplocha, K.; Dmitruk, A. (Applied Surface Science, 2026)
Magnesium alloys are promising materials for biodegradable orthopedic and cardiovascular implants, avoiding second interventions and related complications. Magnesium is a biocompatible and key element for numerous physiological processes; however, its degradation rate is too rapid, accompanied by strong hydrogen development, pH rise, and consequent inflammation. In this context, innovative strategies to modulate the degradation of magnesium and its alloys are an urgent clinical need. Natural green tea polyphenols were explored in this research work as a promising and sustainable strategy for obtaining organic protective coatings on AZ31 and AZ91 Mg-alloys for cardiovascular and orthopedic applications. Coatings were obtained by soaking samples in a water-based polyphenolic solution and characterized by Scanning Electron Microscopy equipped with Energy Dispersive Spectroscopy, Fourier Transformed Infrared Spectroscopy, tape adhesion tests, static soaking degradation tests, electrochemical corrosion measurements, and preliminary cytocompatibility tests. Results suggest that surface preparation plays a crucial role in obtaining stable and homogeneous coatings. In optimized conditions, globular-shaped coatings free of cracks were obtained on both alloys. These coatings significantly reduced the corrosion rate in electrochemical tests and had a protective effect on cells.
CRIS-Team Scopus Importer:2025-12-12
Keywords: Coating; Degradation; Mg-alloys; Polyphenols